Safety citizenship behaviours among the employees in a manufacturing company - Muhammad Syafiq Athir, Husni (2020)
The purpose of this study is to analyze the influence of safety citizenship behavior among the employees in manufacturing organization. This study examined the perception of local and foreign employees in manufacturing company located in Bayan Lepas, Penang on three safety performance variables - safety knowledge, safety motivation, and safety consciousness. A total of 210 questionnaire sets was distributed to the employees in manufacturing company where only 198 sets returned and only 189 sets usable (completed). The findings of this study revealed that safety consciousness has significant correlation with safety citizenship behavior; while safety knowledge and safety motivation were not significantly influence safety citizenship behavior. The findings in this study provide valuable guidance for researchers and practitioners for identifying solutions that can be used to improve safety and health in manufacturing workplace.